Threats in Livelihoods among Adult - Timalsina, Keshab Prasad (International Research Journal of MMC, 2021)
This is a study entitled "threats in livelihood among adult". A major purpose of this study is to assess the level of the threats of livelihood in the near future among the adults. The study was carried out among the Facebook users who were connected with the researcher’s account having at least +2 completed. This is a quantitative study and used cross-sectional descriptive research design to answer research question. Among the users, 113 were selected randomly and survey form prepared in google form share to them for data collection. Researcher succeeded in gathering data from 100 respondents with a 88.5 percent response rate. Collected data were analysed through quantitative methods like; frequency distribution, diagrams, etc. and Mann-Whitney U test and Chi-square test are applied to test the hypothesis formulated in the study. The study found the highest responses from age group 20-24 which consists of 38 percent. Similarly, the study found the highest percentage (54%) in the Brahmin group in the caste/ethnic character of the population and Hindu group in religious characteristics. About 84 percent population used the Nepali language as a mother tongue. Furthermore, about 35 percent study population found completion of Master’s level education and about 47 percent population reported that work problem is the major reason for not involving a further higher level of education. From the study, it is found that all the individuals of the study population has threats of livelihood in the near future. That treats found high in the factor of increasing the price of goods and services but in all the factors threats of livelihood found the medium. The statistical test proved that there is no significant association between threats in livelihood and caste/ethnicity of the study population. Similarly, the study also found that the average level of threats in livelihood does not vary by male and female.